ENGLISH UTTERANCES IN THE STUDYING PROCESS OF LEARNING SUBJECT - Zvarych, Iryna (Mountain School of Ukrainian Carpaty, 2019)
The new technologies growth as well as democracy establishment and the vectors of humanistic progress in Ukraine led to the evolution of students' personalities as the main lever of modern development in the society and state. The main role in shaping modern student personality as a professional one and a citizen belongs to education. Education always reflects the interests of society and fulfills its social orders, forms the public demands for knowledge and progress prospects; changes under the influence of time, social, economic and other factors, demands the education quality service. One of the requirements for the education quality is to adjust students for their profession duties, in particular for study obtaining learning subject knowledge, profession skills and deep knowledge of state language proficiently. This article deals with using utterances, in particular the proverbs, winged statements, sayings for developing the students’ intellectual activity, comprehension of learning subject deeply with popular expressions bearing shadow meanings. The use of utterances makes every nation culture inexhaustible, highlights national history, folk wisdom, outlook of life, worldview; it emphasizes the importance of their usage for the development students’ intellectual abilities, their creative approach to mastering the subject under study. Using the utterances in the studying process encourages students for learning subject thoroughly, creative thinking, the deep shadow understanding of the language statements' meaning. Language is used to express thoughts, conceal the meaning, but the most often to replace thinking and development of students' activity for learning subject properly and it is considered to be a perfect and important means of human communication that helps young generation to share their thoughts, express their feelings, achieve mutual understanding, create spiritual values, in particular, deep comprehension of learning subject, and formation of personality. All people have no greater treasure than their speech, because only their language is the character, memory, spiritual power, history and evolution.